Distribution of nontuberculous mycobacteria in patients with and without HIV/AIDS in Chongqing. (15th March 2022) - Nie, Jingmin; Deng, Xizi; Zeng, Qingling; Du, Xiang; Chen, Yaokai; Hu, Fengyu
Abstract: Introduction: In this study, the distribution of nontuberculous mycobacteria (NTM) strains in patients with and without HIV/AIDS in Chongqing, China was evaluated. Methods: A retrospective study was performed in January–December 2020 at Chongqing Public Health Medical Center. NTM strains were assessed by a multi locus phylogenetic analysis. The distribution of NTM strains in HIV/AIDS and non‐HIV/AIDS groups was compared. CD4+ cell counts, imaging changes, and characteristics of mycobacterial species were determined. Results: In total, 324 patients with NTM infection (50 patients with HIV/AIDS and 274 patients without HIV/AIDS) were included. The most common etiological agent was M .  abscessus (29%), followed by M .  paraintracellulare (12%) and  M .  colombiense (11%). Predominant NTM species were M .  avium (26%), M .  colombiense (24%), and M .  kansasii (18%) in patients with HIV/AIDS and were  M .  abscessus (32%), M .  paraintracellulare (13%), M .  fortuitum (10%), and M . intracellulare (10%) in patients without HIV/AIDS. For a CD4+ cell count of <200/μl, the predominant species were M .  avium in the HIV/AIDS group and M .  abscessus in the non‐HIV/AIDS group. With respect to radiologic characteristics, different NTM strains were associated with distinct imaging manifestations; for example, M .  marseillense, M .  kansasii, and M .  parasenchytosis were more likely to induce cavities. Imaging cavities, bronchiectasis, and acinar‐like changes were more common in the non‐HIV/AIDS groups. Conclusions: The infection rates of HIV and NTM in Chongqing are high, while M .  abscessus, M .  paraintracellulare, and M .  colombiense are the main pathogens causing NTM diseases in Chongqing, and NTM strains differed significantly between patients with and without HIV/AIDS. Monitoring these indicators can help develop prevention strategies.